Mecanismo celulares e estresse oxidativo como marcadores de tolerância para cádmio em Aspergillus nidulans (UCP 1580) - Nascimento, Ana Claudia Claudina do (2013)
Increased pollution / environmental degradation has been observed with a growing concern for global communities , considering its main resulting health problems and significant losses of natural systems . Among the contaminants , heavy metals have been gaining prominence for its toxicity and accumulation in food chains . Among the methods of removing / minimizing metals , bioremediation is gaining momentum as a viable alternative for the treatment of polluted environments . Cadmium is a metal of high toxicity , and induces cellular changes that affect the morphology and activity of polymers and enzyme systems of living systems . However , some systems exhibit tolerance to the presence of cadmium and the study of these changes may provide important data to contribute to the bioremediation of heavy metals . This formal, this proposal aims to evaluate the behavior of oxidative enzymes and total proteins , polyphosphates and cellular structure and sorption of metal ion in Aspergillus nidulans in response to growth in the presence of 1 mM , 2 mM and 3 mM cadmium. The results will serve as input for understanding the metabolic mechanisms associated with survival and maintenance and cell viability , which can be applied in bioremediation of heavy metal contaminated environments protocols . Thus , in order to better understand the potential toxicity of an environmental component and its effects on local biota , one broad view is needed that involves knowledge related to genetics, proteomics , cellular metabolism and higher levels of biological organization, order to make this type of study biomarkers with an essential tool for the management and conservation of the environment .